2009
DOI: 10.1007/s11130-009-0115-2
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Antimicrobial and Antioxidative Properties and Total Phenolics of Two “Endemic” Lamiaceae Species from Turkey: Ballota rotundifolia L. and Teucrium chamaedrys C. Koch

Abstract: This study was designed to examine the in vitro antimicrobial and antioxidant activities and the amount of total phenolics of the methanol extracts of Ballota rotundifolia L. and Teucrium chamaedrys C. Koch. In the case of antimicrobial activity tests, polar sub-fractions of the methanol extracts of plant species exhibited weakest antimicrobial activity when compared with the non-polar ones. While, non-polar sub-fraction of B. rotundifolia showed moderate activity against A. lwoffii, C. perfringens and the yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 28 publications
(29 reference statements)
1
16
0
1
Order By: Relevance
“…Teucrium chamedrys and T. montanum are very rich in phenolic compounds with very strong biological activity and antioxidative effects (Č anadanović- Brunet et al 2006;Ozgen et al 2006;Gursoy and Tepe 2009;Stanković et al 2010;Stanković et al 2011b). Stankovic et al (2011a) reported that extracts from different Teucrium species caused cytotoxicity and induced apoptosis in human HCT-116 cells (human colon cancer cell line), hence they could be considered suitable natural anticancer products.…”
Section: Discussionmentioning
confidence: 99%
“…Teucrium chamedrys and T. montanum are very rich in phenolic compounds with very strong biological activity and antioxidative effects (Č anadanović- Brunet et al 2006;Ozgen et al 2006;Gursoy and Tepe 2009;Stanković et al 2010;Stanković et al 2011b). Stankovic et al (2011a) reported that extracts from different Teucrium species caused cytotoxicity and induced apoptosis in human HCT-116 cells (human colon cancer cell line), hence they could be considered suitable natural anticancer products.…”
Section: Discussionmentioning
confidence: 99%
“…Only some species of this genus have previously been evaluated for antimicrobial activities. Gursoy and Tepe [15] tested polar and non-polar subfractions of methanol extracts of Teucrium chamaedrys from Turkey. The polar sub-fraction exhibited weaker antimicrobial activity than the non-polar samples.…”
Section: Introductionmentioning
confidence: 99%
“…2004). The DPPH assay and β‐carotene/linoleic acid test system were also reported as two complementary tests (Gursoy and Tepe 2009).…”
Section: Resultsmentioning
confidence: 99%